EPIDEMIOLOGICAL AND MYCOLOGICAL STUDIES ON TINEA CAPITIS AT THE NURSERIES AND SCHOOLS OF BANDAR CHABAHAR - F. Zaini; A. Ghagari (Tehran University of Medical Sciences, 1989)
2260 (1755 male and 505 female) preschool and school Children of Chabahar were studied for Tinea capitis and pediculosis of the scalp. 42 cases were found positive in direct Examination, 41cases Endothrix being only one case; was ectothrix. Trixhophyton violaceun was isolated from 40 cases and 4 of those were microscopically negative for fungal elements. Totally, 46 cases of Tinea capitis with prevalence of 2.03 percent were seen. The disease occurred in both sexes, but the vales have shown the highest prevalence (80.45) in comparison with females (19.6%). Highest incidence was shown among children 6-9 years of age (45.65%). Totally 304 cases (13.45%) had pediculosis of the scalp, and highest percentage (78.29%) was in girls, and only in 4 cases Tinea capitis was associated with pediculosis of the scalp.